2020
DOI: 10.3390/rs12233995
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Track Aircraft in Infrared Imagery

Abstract: Airborne target tracking in infrared imagery remains a challenging task. The airborne target usually has a low signal-to-noise ratio and shows different visual patterns. The features adopted in the visual tracking algorithm are usually deep features pre-trained on ImageNet, which are not tightly coupled with the current video domain and therefore might not be optimal for infrared target tracking. To this end, we propose a new approach to learn the domain-specific features, which can be adapted to the current v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Apart from the passive landing marker methods listed above, the active sourced markers presented in some early studies are potential solutions to nighttime landing. Activated landing markers, a large number of which are based on TIR technology that has been widely used for rescue, surveillance, inspection, and automatic target recognition [ 40 , 41 ], are more favorable to operating in bad weather conditions or dark environments. Several studies have suggested deploying infrared-based ground structures and sensors to accommodate the task of landing in poor-illuminated scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from the passive landing marker methods listed above, the active sourced markers presented in some early studies are potential solutions to nighttime landing. Activated landing markers, a large number of which are based on TIR technology that has been widely used for rescue, surveillance, inspection, and automatic target recognition [ 40 , 41 ], are more favorable to operating in bad weather conditions or dark environments. Several studies have suggested deploying infrared-based ground structures and sensors to accommodate the task of landing in poor-illuminated scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The thermal infrared technology has been widely used for rescue, surveillance, and automatic target recognition. Tracking based on this technology is not subject to illumination variations; thus, it can track the target in total darkness [38]. The heat signatures of electrical components captured by the FLIR camera are not affected by the surroundings such as the sky or clouds because the camera is capable of their recognition.…”
Section: Detection Of Structural Damagesmentioning
confidence: 99%
“…Tracking and segmenting small targets on edge devices is a task of great significance, which has a wide range of applications in air traffic management, military reconnaissance, aviation security, and more [1][2][3][4]. Semi-supervised video object segmentation (S-VOS) is a task that only requires the user to specify the object of interest in the first frame and then automatically completes the tracking and segmentation of the target in the subsequent frames.…”
Section: Introductionmentioning
confidence: 99%